(untitled) (Research, Society and Development, 2022)
This article focuses on the response of Brazilian Democracy in the face of the COVID-19 pandemic state that took place in the country, especially in the first half of 2020. Based on the assumption that the Brazilian democratic model is constituted as a strong concept of institutions abstract, we aim to analyze the formation of national democracy and its effectiveness in the face of the social effects caused by the Covid-19 Pandemic. For this, the historical-contextual course of the concept of Democracy was analyzed and, finally, Democracy in Brazil was evaluated from the impacts caused by the Covid-19 Pandemic and the consequences of this action in the realization of the national democratic space. To achieve the arguments, a bibliographic study was used, with scientific data, based on the following bases: Scielo, CAPES and Google Scholar, using the keywords: “Democracy”; “Pandemic” and “Covid-19”. The results showed that with the Pandemic it was realized how Democracy in Brazil is purely formal, reduced to legal and academic concepts. This abstraction has become lethal to the poorer classes, as it has materialized its material inefficiency, which for years has been dismantling social protection structures, denying the poor access to the practical exercise of isonomy and demonstrating the secondary role of legal discourse, creating a gap between what it would be the essence of democracy (justice) and the materialization of this institute in Brazil (class interests). The Pandemic process tends to intensify, but for years it will leave marks on the lower deck of the ship, where the poorest will remain poor, the rich, for sure, will become millionaires.